Prevalence and global trends of polypharmacy in patients with chronic kidney disease: A systematic review and meta-analysis - Naseralallah, Lina; Khatib, Malkan; Al-Khulaifi, Azhar; Danjuma, Mohammed (Frontiers in Pharmacology, 2023)
Background and objectives: Polypharmacy and chronic kidney disease (CKD) are becoming increasingly common due to an ageing population and the rise of multimorbidity. In line with the therapeutic guidelines, managing CKD and its complications necessitates prescribing multiple medications, which predispose patients to polypharmacy. The aim of this systematic review and meta-analysis is to describe the prevalence of polypharmacy in patients with CKD and to explore the global trends of factors driving any apparent variability in prevalence estimates. Methods: PubMed, Scopus, the Cochrane Database of Systematic Reviews (CDSR), and Google Scholar were searched from inception to November 2021. Study selection, data extraction, and critical appraisal were conducted by two independent reviewers. The pooled prevalence of polypharmacy was estimated utilizing the random effects model using the default double arcsine transformation. Results: 14 studies involving 17 201 participants were included in this review. The majority of patients were male (56.12%) with a mean age of 61.96 (SD±11.51) years. The overall pooled prevalence of polypharmacy amongst patients with CKD was 69% (95% CI: 49–86%) (I2=100%, p<0.0001), with a proportionately higher prevalence in North America and Europe as compared to Asia. Conclusion: The pooled prevalence estimates from this synthesis established that polypharmacy is a significant and rising problem among patients with CKD. The exact interventions that are likely to significantly mitigate its effect remain uncertain and will need exploration by future prospective and systematic studies.